A comprehensive interdisciplinary review of mine supply chain management. (December 2021) - Zeng, Lanyan; Liu, Shi Qiang; Kozan, Erhan; Corry, Paul; Masoud, Mahmoud
Abstract: There is an everlasting distance and interdependence between mines and end-users as it involves different types of equipment, infrastructure, and facilities, including excavators, trucks, processing plants, stockpiles, railways, ports, ships, etc. Precise management of a complex mine-to-customer supply chain system is essential to guarantee delivering mineral products from remote mines to overseas clients in a well-organised way. In the literature of mining management, both academic scholars and industrial managers are paying more and more attention to develop state-of-the-art mine supply chain management (MSCM) methodologies. To meet this emerging demand, this study aims to conduct a comprehensive and up-to-date literature review on MSCM research topics by evaluating over 200 papers, mostly published in the last decade (2010–2021). We analyse the characteristics of the reviewed papers from perspectives of the mine supply chain's links and the interdisciplinary classification. Thus, we classify these papers into nine main categories, namely, capacity planning, logistics, inventory control, network design, economic issues (e.g., pricing), efficiency evaluation, risk control, environmental protection, and production scheduling. Based on this classification, we present potential research opportunities and managerial insights in the area of MSCM. Highlights: Over 200 recent papers relevant to mine supply chain management are reviewed. Characteristics of the reviewed papers are analysed in an interdisciplinary way. We classify these papers into nine main categories. Potential research opportunities and managerial insights are provided.